The Analysis of Factors Affecting Burnout Rate in Nurses Working in Adult Nursing Rooms at Hospital - Amini, Fatimah Nur Janah; Setiyadi, Noor Alis; Subrata, Sumarno Adi (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Burnout syndrome is a response to physical and mental fatigue caused by increased workloads and emotionally demanding work situations that can be triggered by prolonged exposure to workplace stress. Nurses who work in nursing rooms and street nurses are potentially stressed by overloaded job demands related to service to others. Burnout syndrome, if not addressed promptly, can have a hazardous impact on health professionals, including reduced performance, such as low responsibility, high risk of medical errors, reduced commitment to work, and high self-stress. One of the efforts that can be made is to measure the level of work stress and the factors associated with it. Therefore, researchers are interested in conducting research that analyzes factors that influence burnout rates among nursing nurses in private hospitals in Surakarta. This type of research is quantitative research with a cross-sectional research design. The sampling technique in this study uses total sampling with a total sample of 47 respondents. The respondents to this study were all the nurses who worked in the adult nursing establishment of the hospital where the research was carried out. The Oldenburg Burnout Inventory questionnaire, which has been adapted into Indonesian, is used to measure the burnout rate of nurses working in adult nursing rooms. The results of the study showed that of the eight factors tested, only two factors influenced the burnout rate of nurses in adult nursing facilities: the working time factor and the length of shift per week (in hours). The p-value of both factors was 0.001. Of the two factors, the time factor was the most influential factor on burnout rates in nurses in adult hospital facilities, with an unstandardized B value of 0.317. While the study examines several demographic and work-related factors potentially associated with burnout, it may overlook other critical determinants. For instance, organizational factors (e.g., leadership support, workload distribution, organizational culture) and individual coping mechanisms could significantly influence nurses' burnout experiences. Future research should consider a more comprehensive range of factors to provide a holistic understanding of burnout in nursing.